CORPORATE GOVERNANCE STRUCTURE AND TIMELINESS OF FINANCIAL REPORT - Gunarsih, Tri (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2011)
The main objectives of this research are to describe the obedience towards the regulation of timeliness financial report submission and to analyze the influence of financial performance and corporate governance structure to timelines of financial report submission. The research questions are tested by running Analysis of Variance (Anova) and two logistic regressions. Timelines (measured by dummy variable, 1 if the company comply financial report submissioni.e. before and at 31 of March, while 0 for delayed submission) is the dependent variable both in Anova and in logistic regression. The independent variables in logistic regression consist of EAT, ROA, ROE, Leverage, concentration ownership by domestic institution, number of the Board of Directors, number of the Board of Commissioners and Industry Classification. The first main result of this study is that there is an increasing of timelines obedience. This suggests that the obedience of listed companies towards the regulation of timelines is increasing form time to time. The second main result of this study is that there is an influence of profitability (ROA), leverage and corporate governance structure (ownership concentration by Domestic Institution/HI_DOM) to the probability of timelines financial report submission. The positive and negative sign of ROA and leverage respectively, suggest that higher ROA and lower leverage tend to obey the regulation of timelines. The negative sign of HI_DOM suggest that the lower ownership concentration by Domestic Institution tend to obey the regulation of timelines.